Effect of interwall interaction on the electronic structure of double-walled carbon nanotubes. (27th March 2015) - Soto, M; Boyer, T A; Biradar, S; Ge, L; Vajtai, R; Elías-Zúñiga, A; Ajayan, P M; Barrera, E V
Abstract: Through this study, the results of density functional theory calculations within the local density approximation of the electronic structure of zigzag–zigzag double-walled carbon nanotubes (DWCNTs), with chiral indices ( n, 0)@( m, 0) for n = 7–15, and m = 15–26, has been presented and the effects of interwall interaction and orbital hybridization on the electronic structure of these systems has been discussed. It was observed that the electronic band gap of the aforementioned DWCNTs depends on the interwall distance only for metallic–semiconductor configurations and on the intrinsic properties of the constituent tubes in all other combinations. It was also observed that the calculated band gap for most of the metallic–metallic DWCNTs was smaller than semiconductor–metallic, metallic–semiconductor, and semiconductor–semiconductor configurations. Metallic–semiconductor DWCNTs were found to be desirable for band gap tuning applications because of their dependence on interwall distance, opening up the possibility of using such systems in electronic device applications, such as transistors. Other applications include the use of DWCNTs in macroscopic carbon nanotube conducting wires, for which metallic–metallic and semiconducting–metallic zigzag–zigzag DWCNTs were found to be the most desirable configurations due to their small band gaps.